Analysis of a refined model for the IEEE 802.11 distributed coordination function. (1st January 2013) - Ahuja, Aditya; Krishna, P. Venkata; Saritha, V.
As the IEEE 802.11 standard WLANs become more and more ubiquitous, a number of studies on the saturation throughput analysis for the distributed coordination function have been presented. In order to reconcile previous differences, and to conform to the actual IEEE 802.11 standard, a new backoff decrement model which takes into consideration anomalous slots has already been proposed, which is rigorously analysed in this paper. Moreover, we present a rough outline of a decision-making framework for finding a policy for a controller to select optimal backoff counter values at different backoff stages.